Why Data Citation Is a Computational Problem. - BUNEMAN, PETER; DAVIDSON, SUSAN; FREW, JAMES (Communications of the ACM, 2016)
The article explores database citation. Particular focus is given to how a citation is a collection of "snippets" of information. Additional topics discussed include how most information online is now published in evolving databases or datasets, how data citation depends on both the query and the data, and MODIS (MODERate-resolution Imaging Spectrometer) data.